Design, synthesis, and evaluation of the novel ozagrel–paeonol codrug with antiplatelet aggregation activities as a potent anti-stroke therapeutic agent - Zuo, Chijing; Yan, Fulong; Wang, Jie; Zhu, Yulong; Luo, Wenhui; Liu, Yan; Liang, Wanhui; Yu, Weidong; Zhang, Jingwei; Peng, Daiyin; Ma, Xiaodong; Peng, Can (Frontiers in Pharmacology, 2024)
Ischemic stroke (IS), with its high morbidity, disability and mortality, is the second most common chronic disease. Thromboembolism and platelet aggregation are the most features of stroke. At present, no standard, accepted, and effective treatment for acute ischemic stroke has been established, other than aspirin. Consequently, it is essential to investigate novel therapeutic compounds. In this study, novel codrugs of ozagrelpaeonol were synthesized and characterized using 1 H-NMR, 13 C-NMR and mass spectroscopy. Their antiplatelet aggregation activity was evaluated, with PNC3 (8b) exhibiting the highest activity. Subsequent studies were conducted to assess its neuroprotective effect, pharmacokinetic properties and protein-molecular interactions.The results indicated that PNC3 has good bioavailability and improved the OGDinduced cell viability. Moreover, molecular docking analysis further demonstrated that the compound interacts with the residues located in the active binding sites of the target protein. Overall, the synthesized codrugs may have promising pharmacological activities and could be developed into an oral formulation.